Using explicit teaching of philosophy to promote understanding of the nature of science: a case study from a Chinese high school - Shi, Xiaoming (Springer Science and Business Media B.V., 2020)
Adopting an explicit and reflective approach to the teaching of the history and philosophy of science is useful in promoting high school students’ understanding of the nature of science. Whereas the history of science is usually signposted clearly in the school science curriculum, the philosophy of science is considered to be embedded in and integral to science education. This article argues that philosophical topics also need to be explicitly signposted and discussed in the teaching of the nature of science in high schools. This study investigates an interdisciplinary course on the nature of science in a Chinese senior high school. The course involved explicit teaching of philosophy of science topics with subject knowledge in each lesson. This mixed method design of the research included a modified version of the Views on Science, Technology and Society questionnaire as reported by Aikenhead and Ryan (Science Education, 76(5):477‑491, 1992) and phenomenographical analysis. Although the sample size is small, the results suggest that explicit teaching of philosophy of science topics helps students better understand both the nature of science and the relationship between science, technology and society.